Efeito da angulação facial sobre o reconhecimento de expressões faciais e atribuição de intensidade emocional - Leime, Jamila Leão (2015)
This research aimed to investigate the effect of multiangularity of emotional facial expressions in the recognition and assignment of emotional intensity task. Three studies were conducted: 1) composition of a multiangular facial expressions set, 2) development of a set of 3D expressions and 3) comparison of recognition rates and assigning intensity of frontal facial expressions in relation to the left side ones in young adults. The results show 1) difficulties in obtaining three-dimensional faces, 2) the angle did not affect the recognition of expressions, 3) allocation of lower intensities for the left emotions and male faces, 4) best female performance in the recognition task, 5) increased recognition of women's faces and 6) less recognition of male faces. It was concluded that the ability to recognize emotions in facial expressions occurs regardless of the gender of the observer and the facial angle.